Chimeric antigen receptor T-cell therapy for B-cell non-Hodgkin lymphoma: opportunities and challenges - Shinichi Makita; Katsuaki Imaizumi; Saiko Kurosawa; Kensei Tobinai (BioExcel Publishing Ltd, 2019)
B-cell non-Hodgkin lymphoma (NHL) is the most frequent hematologic malignancy. Despite the refinement of chemoimmunotherapy, a substantial number of patients experience chemorefractory disease. Anti-CD19 chimeric antigen receptor (CAR) T-cell therapy is considered the most promising and effective therapy to overcome chemorefractory B-cell NHL. Based on the promising results obtained from pivotal trials, the US Food and Drug Administration and European Medicines Agency approved anti-CD19 CAR T-cell therapy for relapsed/refractory diffuse large B-cell lymphoma. Nonetheless, there remain several controversial issues and problems awaiting solutions, including optimal management of toxicities, overcoming relapsed/refractory disease after CAR T-cell therapy, and improving CAR-T manufacturing platform. Definite unmet medical needs among patients with chemorefractory B-cell NHL still exist. CAR T-cell therapy might be a game changer that can defeat chemorefractory B-cell NHL, and further clinical development is warranted. In this review, we summarize the recent clinical developments, clinical implications, and perspectives of CAR T-cell therapy, focusing on B-cell NHL.